ANALISIS PENGARUH PERILAKU KONSUMEN PADA INFLUENCER MARKETING DAN PACKAGING PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK REYSHAKA INTERIOR - Zahroh, Fathimatuz; Ruswaji, Ruswaji; Susanti, Ike; Sustyorini, Emalia Nova (Universitas Nusa Cendana, 2024)
This study seeks to assess the influence of influencer marketing and product packaging on the purchasing decision of the Reyshaka Interior product. The research used a quantitative descriptive design. The survey included 270 participants, including a sample of 100 long-time consumers of Reyshaka Interior. Data gathering methods entail distributing surveys to participants. Partial Least Squares Structural Equation Modeling (PLS-SEM) is employed for data analysis. The study started in November 2023 and was completed in March 2024. The study reveals that influencer marketing and product packaging significantly influence purchase decisions for the Reyshaka Interior product. The predominant element is the influencer marketing variable, which surpasses consumer behavior. Consumer behavior can significantly influence purchasing decisions through influencer marketing and products. Keywords: Influencer Marketing; Product Packaging; Purchasing Decision